Bisakah Alam Menjadi Subyek Hukum? Refleksi Atas Beberapa Pengalaman - Prabowo, Rian Adhivira; Seno, Adi; Setiawan, Fajar Ahmad; Herlambang, Unu P.; Ermansyah, Edho R.; Ginting, Gerry Pindonta (UI Scholars Hub, 2023)
This paper discusses three legal precedents regarding the legal personhood of nature in three countries; Ecuador, New Zealand, and India. Each country has recognized some natural areas as legal persons through different means. In Ecuador, the rights of nature, which resemble legal personhood of the nature, are recognized in the 2008 Amendment of Ecuador Constitution. Meanwhile, New Zealand has recognized the legal personhood of Whanganui River through legislated settlement treaty between the government and Maori peoples. Whereas in India, the rivers of Ganges and Yamuna have been recognized its legal personhood through the Uttarakhand High Court’s decisions. These three legal precedents are a very important breakthrough in legal studies regarding “who”, “whom” and now “what”, are recognized as a legal person. This article contains descriptions of the three precedents aforementioned which will be explored further in terms of possible advantages and also weaknesses that came with by recognizing nature as legal person.